Life is beautiful - Benigni, Robert 1952-; Ferri, Elda; Brashi, Gianluigi 1963-2008; Braschi, Nicoletta 1960- (Miramax Home Entertainment, 1998)
In this extraordinary tale, Guido - a charming but bumbling waiter who's gifted with a colorful imagination and irresistible sense of humor - has won the heart of the woman he loves and created a beautiful life for his young family. But then, that life id threatened by World War II...and Guido must rely on those very same strengths to save his beloved wife and son from an unthinkable fate! Honored with an overwhelming level of critical acclaim, this truly exceptional, utterly unique achievement will lift your spirit and capture your heart!